Construction and characterization of a Lactococcus lactis in-trans surface display system harboring murine glycosylated tyrosinase related protein-2 - Kalyanasundram, Jeevanathan (2015)
Food and commensal lactic acid bacteria (LAB) surface display system exploitation for bacterial, viral, or protozoal antigen delivery has received immense interest currently. The Generally Regarded as Safe (GRAS) status of LAB such as Lactococcus lactis coupled with non-recombinant strategy of in-trans surface display system, provide a safe platform for therapeutic drug and vaccine development. However, therapeutic proteins fused with cell-wall anchoring motif production are predominantly limited to prokaryotic expression system. This presents a major disadvantage in surface display system particularly when glycosylation has been recently identified to significantly enhance epitope presentation. In this study,glycosylated murine Tyrosinase related protein-2, mTRP-2, tumor associated antigen anchoring to L. lactis cell wall was attempted. The mtrp-2-cA (AcmA, peptidoglycan anchoring motif) fusion gene expression in Chinese Hamster Ovary, CHO cells was carried out. Initial CHO cell expression of both native mtrp-2 and mtrp-cA was a failure. Codon optimized mtrp-2 and cA genes also did not result in target protein production. In order to investigate post-translational modification interruption, expression of codon optimized mtrp-2125-276 epitope devoid of mtrp-2 native maturation signal peptide was performed which resulted in misfolded plus aggregated mTRP-2125-276 and mTRP-2125-276 –cA protein production. Successful expression of both mtrp-2125-276 and mtrp-2125-276 -cA genes suggest CHO cell’s endoplasmic reticulum signal peptidase inability to recognize mTRP-2 signal peptide cleavage site. The following substitution of native mTRP-2 signal peptide with Chinese Hamster TRP-2 signal peptide, CHsp resolved this issue by successful expression of soluble mTRP-2 and mTRP-2-cA by CHO cells in both intracellular and extracellular fraction. A total amount of 40 μg of mTRP-2-cA protein from 2.7 g in wet weight of CHO cells was purified and detected to be glycosylated by glycoprotein staining. Subsequent mTRP-2-cA anchoring to the cell wall of L. lactis showed excitation of FITC conjugate on secondary antibody which signified successful binding of glycosylated TRP-2 on the surface of L. lactis.